The Effect of CBT Group Counseling Cognitive Restructuring Techniques and Behavior Contract Techniques on Increasing Adolescent Coping Stress - K Khoirunnisha; Paramita Nuraini; I Indiati (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to examine the effect of Cognitive Behavior Therapy (CBT) group counseling, cognitive restructuring techniques and behavioral contracting techniques on increasing stress coping in adolescents. This study used a randomized pretest-posttest comparison group design. The samples taken in this study were 13 adolescents consisting of 6 adolescents as experimental group 1 with cognitive restructuring technique and 7 adolescents as experimental group 2 with behavioral contract technique. Sampling using random sampling technique. The method of data collection was done by using a stress coping questionnaire. The data analysis method used is One Way Anova parametric analysis. The results showed that Cognitive Behavior Therapy (CBT) group counseling, cognitive restructuring techniques and behavioral contracting techniques had an effect on increasing stress coping in adolescents. These results are evidenced by the results of the One Way Anova Parametric Statistics test with a probability value of sig (2-tailed) 0.001 < 0.05. Based on the analysis and discussion, there is an increase in the average score of the coping stress questionnaire between the experimental group 1 with cognitive restructuring techniques by 23.77% and experimental group 2 with behavioral contracting techniques by 15.47%. The results of the study can be concluded that Cognitive Behavior Therapy (CBT) counseling with cognitive restructuring techniques has more effect on increasing coping stress in adolescents compared to behavioral contracting techniques.